# Note: Enter your answer and show all the steps that you use to solve this problem in the space provided.

x

2

1
0 1 2
y
Use the function rule to complete the table.

10
x
+
y
=
4

1. 👍
2. 👎
3. 👁
4. ℹ️
5. 🚩
1. halp me plz

1. 👍
2. 👎
3. ℹ️
4. 🚩
2. stop sir plz

1. 👍
2. 👎
3. ℹ️
4. 🚩
3. S
e
e

h
o
w

a
n
n
o
y
i
n
g

v
e
r
t
i
c
a
l

t
e
x
t

i
s
?

1. 👍
2. 👎
3. ℹ️
4. 🚩
4. Y
u
p
,

@
o
o
b
l
e
c
k
,

I

s
e
e

t
h
a
t.

h
e
t
e
x
t

i
s
v
e
r
t
i
c
a
l

c
u
z

t
h
e
y

c
o
p
i
e
d

a
n
d

p
a
s
t
e
d

a
n

e
q
u
a
t
i
o
n

a
n
d

t
h
e

e
q
u
a
t
i
o
n
s

l
o
s
e

t
h
e
i
r

f
o
r
m
a
t
t
i
n
g

a
n
d

g
e
t

a
l
l

f
u
n
k
y
.

1. 👍
2. 👎
3. ℹ️
4. 🚩
5. AWNSER THE QUESTION LZ

1. 👍
2. 👎
3. ℹ️
4. 🚩
6. y = 10 x + 4
(-2, -16)
(-1 , -6)
(0 , +4}
(1 , 14)
(2 , 24)

1. 👍
2. 👎
3. ℹ️
4. 🚩
7. i thought i was out of luck finding answers till i saw Heyo, if its correct, thank you!

1. 👍
2. 👎
3. ℹ️
4. 🚩
8. thanks i think @heyo is correct i will try and find the second answer for all of you :) so you can lazy lol

1. 👍
2. 👎
3. ℹ️
4. 🚩
9. for the first one:
rewrite it as y = 10x + 4 , (since you need the y values, express the
equation in terms of y)
now just sub in the given x values
e.g.
if x = -2 , y = 10(-2) + 4 = -20+4 = -16
if x = -1, y = 10(-1) + 4 = -10+4 = -6
..
if x = 2 , y = 10(2) + 4 = 20+4 = 24

for the second, did you notice that over every increase of 1 in the x
the y decreases by 5
so it must be y = -5x + b
now just use one of the points , e.g. (2, -11)
-11 = -5(2) + b
-11 = -10 + b
- 1 = b

your function is y = -5x - 1

credit goes to @mathhelper
these are the first and second answers :) your welcome have a good day/night

1. 👍
2. 👎
3. ℹ️
4. 🚩